2015
DOI: 10.1016/j.bbr.2015.03.058
|View full text |Cite
|
Sign up to set email alerts
|

The 6-OHDA mouse model of Parkinson's disease – Terminal striatal lesions provide a superior measure of neuronal loss and replacement than median forebrain bundle lesions

Abstract: Unilateral 6-hydroxydopamine (6-OHDA) lesions of the nigrostriatal pathway produce side-biased motor impairments that reflect the motor deficits seen in Parkinson's disease (PD). This toxin-induced model in the rat has been used widely, to evaluate possible therapeutic strategies, but has not been well established in mice. With the advancements in mouse stem cell research we believe the requirement for a mouse model is essential for the therapeutic potential of these and other mouse-derived cells to be efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 34 publications
6
29
0
1
Order By: Relevance
“…degeneration of the DA neuron in C. elegans, including foodsensing behavior and the shortened lifespan. These results are consistent with the previous studies that have reported 6-OHDA-induced parkinsonism in both in vitro and in vivo models (Latchoumycandane et al, 2011;Bagga et al, 2015;Chalorak et al, 2018). 6-OHDA selectively induced the toxicity in the DA neurons by entering the cell through dopamine transporter which expressed exclusively in the DA neuronal cell surface (Nass et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…degeneration of the DA neuron in C. elegans, including foodsensing behavior and the shortened lifespan. These results are consistent with the previous studies that have reported 6-OHDA-induced parkinsonism in both in vitro and in vivo models (Latchoumycandane et al, 2011;Bagga et al, 2015;Chalorak et al, 2018). 6-OHDA selectively induced the toxicity in the DA neurons by entering the cell through dopamine transporter which expressed exclusively in the DA neuronal cell surface (Nass et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Having ascertained the neuroprotective effects of TG-DHA in cell models, we studied an animal model, the 6-OHDA-lesioned mouse. We performed the 6-OHDA lesion in the striatum as it has been reported that striatal lesions lead to reliable, effective and retrograde degeneration of dopaminergic neurons within the substantia nigra pars compacta ( Bagga et al, 2015 ; Becker et al, 2017 ), thus mimicking better the disease-associated temporal dopaminergic denervation ( Deumens et al, 2002 ). Interestingly, we found that concomitant and subsequent chronic administration of TG-DHA completely prevented 6-OHDA-mediated striatal dopaminergic cell death; furthermore, treated mice exhibited similar motor skills to those of non-lesioned control mice.…”
Section: Discussionmentioning
confidence: 99%
“…For the studies employing FluoroGold, the tracer was delivered one week before 6-OHDA infusions in the same striatal location so that retrograde uptake by healthy dopaminergic neurons could proceed in an unimpeded fashion. The doses chosen for 6-OHDA and FluoroGold are consistent with or lower than doses reported in the recent literature (Bagga et al, 2015; Cohen et al, 2011; Lazzarini et al, 2013; Liang et al, 2008), and were also based on our own pilot studies to ensure lack of striatal necrosis. The needle was withdrawn 4 min after the infusion was completed to minimize diffusion into dorsal structures during withdrawal.…”
Section: Methodsmentioning
confidence: 95%